2021
DOI: 10.1007/s11356-021-16576-6
|View full text |Cite
|
Sign up to set email alerts
|

Biochar and slow-releasing nitrogen fertilizers improved growth, nitrogen use, yield, and fiber quality of cotton under arid climatic conditions

Abstract: The efficiency of nitrogenous fertilizers in South Asia is on a declining trajectory due to increased losses. Biochar (BC) and slow-releasing nitrogen fertilizers (SRNF) have been found to improve nitrogen use efficiency (NUE) in certain cases. However, field-scale studies to explore the potential of BC and SRNF in south Asian arid climate are lacking. Here we conducted a field experiment in the arid environment to demonstrate the response of BC and SRNF on cotton growth and yield quality. The treatments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 54 publications
1
17
1
Order By: Relevance
“…The higher seed cotton yield and mung bean yield increased the net benefits and, ultimately, economic benefit ratio. The results and findings showed the significance of the issues, as similar aspects have been investigated in previous studies, under arid to semi-arid climatic conditions [56][57][58][59][60][61].…”
Section: Discussionsupporting
confidence: 81%
“…The higher seed cotton yield and mung bean yield increased the net benefits and, ultimately, economic benefit ratio. The results and findings showed the significance of the issues, as similar aspects have been investigated in previous studies, under arid to semi-arid climatic conditions [56][57][58][59][60][61].…”
Section: Discussionsupporting
confidence: 81%
“…It has also positive influence on the reduction of the N losses by controlling nitrate leaching and carbon sequestration in the soil layers (Kammann et al 2011 ; Shafqat et al 2019 ; Steiner et al 2008 ). Cotton crop has showed higher nitrogen use efficiency with the application of biochar which is attributed to increased microbial activity and N cycling in the soils (Basso et al 2013 ; Manzoor et al 2021 ). Furthermore, it reduces pollutants from the environment and can be used as an ecofriendly alternative to synthetic fertilizers (Bashir et al 2021 ; Ijaz et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it reduces pollutants from the environment and can be used as an ecofriendly alternative to synthetic fertilizers (Bashir et al 2021 ; Ijaz et al 2020 ). Slow release N fertilizers are also used to reduce the nitrogen losses as they slowly release nitrogen and stabilize it for efficient utilization (Cantarella et al 2018 ; Manzoor et al 2021 ). Hence, nitrogen losses can be reduced through biochar application (Mandal et al 2016 ; Rasuli et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Moosavi et al [54] showed that the cultivation of cowpea with biochar enhanced the seed number per plant due to the relief of water-deficient stress and a higher phosphate and potassium content. Other studies also endorsed that biochar and nitrogen fertilizer improved the yield-related characteristics in arid climates [55,56]. On the basis of the findings from this study, it is recommended that the use of such soil conditioning materials is helpful for the sustainable production of crops in areas of limited water availability and could also be helpful for the community of the farmers for sustainable production under arid climatic conditions.…”
Section: Discussionmentioning
confidence: 56%